(untitled) (International Journal of Engineering and Computer Science, 2017)
A mobile ad-hoc network is a Temporary wireless network that can be formed without the need for any pre-existing infrastructure in which each node can act as a router. One of the main challenges of mobile ad-hoc network (MANET) Is the design of robust routing algorithms that adapt to the frequently and randomly changing network topology. A variety of routing protocol has been proposed and several of them has been extensively simulated or implemented as well. In this paper, compare and evaluate the performance of two types of on-demand Reactive routing protocol for MANET.-Ad-hoc On demand Distance Vector (AODV) Routing Protocol. Which is unipath and multipath ad-hoc On Demand Distance Vector (MAODV) Routing Protocol. this paper investigates all these reactive routing protocols corresponding to Packet delivery fraction (PDF), Packet loss, Number of packet dropped, Average end-to-end delay. The NS-2 Simulation results showed that AODV has Always low compare to MAODV In both statics and dynamic network for each set of connection. All these case MAODV is a better efficiency analyzed varying to pause time, but worst in case of end-to-end delay